Influência da inibição da enzima cox-2 no processo de reparo de enxertos ósseos autógenos intramembranosos e endocondrais - Moreschi, Eduardo (2012)
Success of alveolar reconstructions using onlay autogenous block boné grafts depends basically on their adequate integration to the recipient bed, characteristics of the graft, from endochondral (EC) or intramembranous (IM) embryologic origins, influenced by a number of local molecules. Considering the fundamental role of cyclooxygenase (COX-2) in bone repair, the aim of the present study was to analyze the effect of its inhibition in the incorporation of iliac crest (EC) and calvaria (IM) bone grafts. Thirty two male rabbits were divided into two groups: Control (EC and IM) treated with saline solution, and Nonsteroidal antiinflammatory drug - NSAID (EC and IM) treated with 6mg/Kg - etoricoxib, to be euthanized after 7, 14, 30 and 60 days. The percentage of new formed bone in the interface area of the IM control grafts was of 14%, when more intense Core binding factor 1 (Cbfa1/Runx2) labeling was registered, against 4.75% of NSAID group at day 14 (P<0.05). No differences were detected between the EC grafts in both situations, although NSAID group presented a more intense Cbfa1/Runx2 labeling at days 14 and 30. No Vascular endothelial growth factor (VEGF) labeling differences were detected. It is suggested that inhibition of COX-2 influences osteogenic activity of onlay bone grafts but does not impair their healing.